2018
DOI: 10.1186/s12992-018-0363-8
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of early neonatal mortality in Afghanistan: an analysis of the Demographic and Health Survey 2015

Abstract: BackgroundNeonatal mortality is declining slowly compared to under-five mortality in many developing countries including Afghanistan. About three-fourths of these deaths occur in the early neonatal period (i.e., the first week of life). Although a number of studies investigated determinants of early neonatal mortality in other countries, there is a lack of evidence regarding this in Afghanistan. This study investigated determinants of early neonatal mortality in Afghanistan.MethodsData from the Afghanistan Dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
102
3
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(129 citation statements)
references
References 54 publications
22
102
3
2
Order By: Relevance
“…Preterm newborn babies were 3.36 times more likely to develop neonatal sepsis compared to term newborns. This finding is in line with studies done in Tanzania [28], USA [29,31] and China [32]. The possible explanation is that preterm babies have immature immune Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Preterm newborn babies were 3.36 times more likely to develop neonatal sepsis compared to term newborns. This finding is in line with studies done in Tanzania [28], USA [29,31] and China [32]. The possible explanation is that preterm babies have immature immune Fig.…”
Section: Discussionsupporting
confidence: 92%
“…This study showed that the odds of neonatal death among neonates with birth size perceived by their mothers as smaller than average was 1.61 times more than neonates with birth size perceived by their mother as average. This finding is similar with studies done Ethiopia (33) and Afghanistan (34). The possible justification might be due to smaller than average birth size neonates indicate low birth weight babies and may result from premature births that increased the risk immune immaturity that predispose for infections, mental retardation, hypothermia and other complication (35).…”
Section: Multilevel Logistic Regression Analysissupporting
confidence: 90%
“…The study also showed women giving birth at or before 18 years of age ((AOR 1.8; 95% CI 1.1-3.2) and ≥ 35 years (AOR 1.7; 95% CI 1.3-2.3) had higher risk for neonatal mortality than 19-34 year women. Women with interpregnancy interval of less than 2 years (AOR 2.6, 95% CI 1.3-4.9) had risk for neonatal mortality than those who gave birth in more than 2-year interval (Kibria et al 2015). A further analysis of 2013 Nigeria DHS showed a difference in neonatal mortality between the urban and rural population.…”
Section: Discussionmentioning
confidence: 92%